Geoinformation system for monitoring the state of river waters - Zamikhovska, Olena; Zamikhovsky, Leonid; Levitsky, Ivan; Nikolaychuk, Mykola (Transfer of innovative technologies, 2021)
Insufficient and untimely forecasting of the level of floods, floods and mudslides, as well as the lack of a modern, full and integrated protection complex lead to annual losses in the agricultural, industrial and social sectors of the economy, as well as human casualties. (30 people in 2008 in Ukraine). The floods of 1969, 1974, 1980, 2000, 2008, 2019, and 2020 were the most negative. At the same time, the flooding of the territories that took place in the Ivano-Frankivsk region in 2000-2008 caused damage to the facilities and the population of the region in the total amount of more than 5.2 billion hryvnias. Despite a number of existing systems for monitoring and forecasting the level of flood waters, such as "TISA", "Prykarpattya", "AXON", etc., they have not found wide practical application due to low efficiency, high cost and disregard. -management of water-physical properties of soils. In this regard, the task of developing systems for monitoring and forecasting the level of flood waters in order to prevent or reduce possible losses in the agricultural, industrial and social sectors of the economy from their negative consequences remains relevant.